Uneven declines between corals and cryptobenthic fish symbionts from multiple disturbances - Catheline Y. M. Froehlich (Nature Portfolio, 2021)
Abstract With the onset and increasing frequency of multiple disturbances, the recovery potential of critical ecosystem-building species and their mutual symbionts is threatened. Similar effects to both hosts and their symbionts following disturbances have been assumed. However, we report unequal declines between hosts and symbionts throughout multiple climate-driven disturbances in reef-building Acropora corals and cryptobenthic coral-dwelling Gobiodon gobies. Communities were surveyed before and after consecutive cyclones (2014, 2015) and heatwaves (2016, 2017). After cyclones, coral diameter and goby group size (i.e., the number of gobies within each coral) decreased similarly by 28–30%. After heatwave-induced bleaching, coral diameter decreased substantially (47%) and gobies mostly inhabited corals singly. Despite several coral species persisting after bleaching, all goby species declined, leaving 78% of corals uninhabited. These findings suggest that gobies, which are important mutual symbionts for corals, are unable to cope with consecutive disturbances. This disproportionate decline could lead to ecosystem-level disruptions through loss of key symbiont services to corals.